EARLY MEDIEVAL BURIAL GROUND GUSARA I IN NORTH OSSETIA - Kadzaeva, Zalina Petrovna; Kanukova, Maria Maratovna (History, Archeology and Ethnography of the Caucasus, 2020)
In 2003 the Alagir archaeological team of the Institute of History and Archaeology (IHA) at Khetagurov North Ossetian State University (now the IHA of the Republic of North Ossetia-Alania) carried out excavation works at the Gusara I burial ground in the Alagirsky district of the Republic of North Ossetia-Alania. A destroyed and looted part of approximately 70 square meters of the burial ground was studied. In total, three underground catacombs were excavated. They contained a little, but quite extensive archaeological material (fibulae, buckles, beads, etc.). The studied catacombs are built in the T-shaped catacombs of type I. There are two varieties of burials according to the details of its constructions: 1) the entrance pits are narrow and long; the bottom of the entrance pit and the chamber are at the same level, the dromos is not expressed, the vault of the chamber is flat. The chambers are small, most likely intended for the burial of a single person. Presumably, the buried people were put with their heads to the left of the entrance; 2) the entrance pit is short; a step separated the bottom of the entrance pit from the bottom of the chamber; the dromos is expressed; the vault is designed in the form of an arch; a bed of organic origin under the buried is traced. The buried lay with their heads to the left of the entrance; an artificially deformed skull was recorded. According to the funerary rite and equipment, investigated underground catacombs belong to the early medieval stage of the Alan culture in the North Caucasus during the second half of the VI – the first half of the VII centuries A.D. The studied archaeological inventory resembles the materials of both early Alan culture and the Hun period. The aim of the article is to present the archaeological materials of Gusara I to the scientific community.